Urbanisasi Pada Kalangan Remaja di Desa Jerora - Tasya Damaya; Kristin Apriliani Puspita Putri; Marini Marini; Annisa Rizqa Alamri; Veronica Egenia Aulia Fiani; Janiva Vera (Universitas Muhammadiyah Sumatera Utara, 2023)
Urbanization is the process of moving people from villages to cities. This phenomenon has become a global trend in recent decades, including among teenagers. The high level of urbanization is also influenced by a better level of progress in urban areas which are used as places of urbanization from an economic and educational point of view. Urbanization can provide new opportunities for young people to access better education and jobs. This study aims to understand and also know about the analysis of urbanization that occurs among adolescents in Jerora village. The analytical tool used in this study is the concept according to Shogo Kayono, where this theory can see how the process of urbanization among adolescents and the positive and negative impacts of urbanization. This study also discusses the pull factors and drivers of the urbanization of adolescents in Jerora village. This study uses qualitative research methods and selects youth from Jerora village who are gray to serve as informants for this research. The data analysis technique used was interviewing, which this technique was interviewed carried out through questions that were asked verbally to respondents and also carried out face to face. The results showed that the urbanization that occurred among adolescents in Jerora village had significantly impacted the economy. By doing this urbanization, they could get decent jobs and be able to continue their education to a higher level. Keywords: urbanization, youth, factors